NILAI-NILAI PENDIDIKAN DALAM UPACARA RAJASWALA - IGA Desy Wahyuni (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
The implementation of Manusa Yadnya ceremony (holy worship to human being) frombirth to adulthood is a Sinangaskara or purification activities performed by parents. Rajaswala’sceremony by Hindus religiously aims to bring out the nature of manhood in human beings andeliminate the nature of Sadripu that resides within man (nature of the faction). As a function ofeducation Rajaswala’s ceremony has a very important role as the affirmation of children, thatchildren have become a child or teenager adult. Thus, they need to be given discourse whichstates that he has grown up, because whatever he did will also result in his parents.